Probiotic consortia are not uniformly effective against different amphibian chytrid pathogen isolates. Issue 2 (8th January 2018) - Antwis, Rachael E.; Harrison, Xavier A.
Abstract: Symbiotic bacterial communities can protect their hosts from infection by pathogens. Treatment of wild individuals with protective bacteria (probiotics) isolated from hosts can combat the spread of emerging infectious diseases. However, it is unclear whether candidate probiotic bacteria can offer consistent protection across multiple isolates of globally distributed pathogens. Here, we use the lethal amphibian fungal pathogen Batrachochytrium dendrobatidis to investigate whether probiotic richness (number of bacteria) or genetic distance among consortia members influences broad‐scale in vitro inhibitory capabilities of probiotics across multiple isolates of the pathogen. We show that inhibition of multiple pathogen isolates by individual bacteria is rare, with no systematic pattern among bacterial genera in ability to inhibit multiple B. dendrobatidis isolates. Bacterial consortia can offer stronger protection against B. dendrobatidis compared to single strains, and this tended to be more pronounced for consortia containing multiple genera compared with those consisting of bacteria from a single genus (i.e., with lower genetic distance), but critically, this effect was not uniform across all B. dendrobatidis isolates. These novel insights have important implications for the effective design of bacterial probiotics to mitigate emerging infectious diseases.